2023
DOI: 10.1002/jsp2.1274
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's Jelly mesenchymal stromal cell‐derived extracellular vesicles promote nucleus pulposus cell anabolism in an in vitro 3D alginate‐bead culture model

Veronica Tilotta,
Gianluca Vadalà,
Luca Ambrosio
et al.

Abstract: BackgroundIntradiscal transplantation of mesenchymal stromal cells (MSCs) has emerged as a promising therapy for intervertebral disc degeneration (IDD). However, the hostile microenvironment of the intervertebral disc (IVD) may compromise the survival of implanted cells. Interestingly, studies reported that paracrine factors, such as extracellular vesicles (EVs) released by MSCs, may regenerate the IVD. The aim of this study was to investigate the therapeutic effects of Wharton's Jelly MSC (WJ‐MSC)‐derived EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…In addition, there is very little literature reporting long-term imaging evaluations of discs treated with chemonucleolysis (Supplemental item 4 ), and long-term clinical outcomes and more objective assessments remain largely undetermined 88 . Therefore, future work may consider revising the enzymatic destruction of herniated disc tissue through supplementation with regenerative treatments 16 , 89 , 90 e.g., co-injection of cells 91 , 92 , biomaterials 93 , 94 , extracellular vesicles 95 , 96 , or platelet-rich plasma (PRP) 97 to support the restoration of the disc over time, particularly regarding younger patients 16 , 79 . For example, previous animal studies have shown the capacity of PRP products to reverse condoliase-mediated disc deterioration 98 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is very little literature reporting long-term imaging evaluations of discs treated with chemonucleolysis (Supplemental item 4 ), and long-term clinical outcomes and more objective assessments remain largely undetermined 88 . Therefore, future work may consider revising the enzymatic destruction of herniated disc tissue through supplementation with regenerative treatments 16 , 89 , 90 e.g., co-injection of cells 91 , 92 , biomaterials 93 , 94 , extracellular vesicles 95 , 96 , or platelet-rich plasma (PRP) 97 to support the restoration of the disc over time, particularly regarding younger patients 16 , 79 . For example, previous animal studies have shown the capacity of PRP products to reverse condoliase-mediated disc deterioration 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative strategies aim to employ cell-free methods to utilize the signaling factors produced by regenerative cell populations [ 132 , 133 , 134 ], particularly their extracellular vesicles (EVs) [ 135 , 136 , 137 , 138 ]. Research demonstrates that EVs derived from NCs contain potent bioactive molecules capable of modulating cellular behavior and are potentially able to promote tissue repair [ 139 , 140 ].…”
Section: Potential Therapeutic Strategies: Taking Inspiration From Np...mentioning
confidence: 99%
“…In the last decade, the possibility to directly tackle the pathophysiology of IDD by replenishing the disc cell content via transplantation of de novo cells has gained significant momentum in the field 4 . Several preclinical studies have demonstrated the capacity of transplanted cells, especially mesenchymal stromal cells (MSCs), to limit, halt, or even reverse IDD both in vitro and in vivo, variably reporting significant enhancements of cell metabolism, matrix composition, and inflammation inhibition, eventually leading to structural restoration of degenerative discs 5–7 . Therefore, the increasing body of preclinical evidence has promoted the translation of cell therapy for IDD to the clinical setting, with multiple prospective clinical trials emerging over the last few decades 8 .…”
Section: Introductionmentioning
confidence: 99%